Organização, estrutura e funcionamento dos Conselhos Municipais de Saúde de Minas Gerais - Ederson Alves da Silva (2021)
Introduction: The Health Councils have assumed permanent responsibility in the public management of health policies, overseeing the application of health resources, controlling the execution of health programs, monitoring economic and financial aspects, analyzing the health plan, and monitoring the implementation of Health Conference guidelines in each government sphere. Social participation in the health area is mostly due to health councils, which are regulated by the Law No. 8142 of 1990, that guarantees community participation in the management of SUS (Unified Health System), and by the Resolution 453 of May 10, 2012, that establishes the guidelines for the institution, reformulation, restructuring and functioning of the Health Councils. The public importance of the Health Councils lies in the requirement for them to function, so that federal government resources related to health are transferred to municipalities and states. However, numerous situations have made this transference difficult to the performance of councils and their respective advisers, in view of their functions. It is necessary to recognize the heterogeneous nature of Health Councils in Brazil and analyze how structural, organizational and functional aspects influence the council's dynamics, as well as the potential of its deliberations. Objective: To analyze the organization, functioning and structure of municipal health councils in Minas Gerais. Methodology: This is a cross-sectional, descriptive study with a quantitative approach. The data collection took place between August and September of 2020. The database was collected directly through the Register of Health Councils of the State of Minas Gerais available online, in the format of tables that can be viewed by Excel, that were in sequence treated and included for analysis in the EPIINFO software, version 7.0. Results: The records come from 842 Municipal Health Councils in the State of Minas Gerais. Only 612 had the parity required by Law 8142/90. The total number of Councilors in the State are 17.137, with a total of 8,459 representatives from the users segment, 4.143 representatives from the workers segment, 1.885 representatives from service providers and 2.598 managers. The Southern Macro Region of the State has the largest number of Municipal Councils, with a total of 147. The Minas Triangle region had the lowest number of Municipal Councils, that is 26 (North Triangle). It should be noted that the most Municipal Health Councils don’t have their own headquarters for their operation, with only 113 registered having their own headquarters and 724 don’t have their own headquarters. About the regarding budget allocation, 592 Councils don’t have their own budget. Also, the Executive Secretariat has 766 councils that have registered the presence of a secretary. About the qualification, only 359 State of Minas Gerais Municipal Councils offer training programs for directors. In addition, the 108 councils don’t have table Director and 235 doesn’t realize election. Conclusions: In conclusion, there is a significant number of health counselors, but the functional structures are still not sufficient to guarantee the autonomy of the health councils and the effective participation of the population in decision-making in the management of the SUS. Keywords: Social Control; Social Participation; Health Council.